RETROSPECTIVE STUDY: CHARACTERISTICS OF SKIN DISEASE IN GERIATRIC PATIENTS AT THE DERMATOLOGY VENEREOLOGY DEPARTMENT OF DR. M. DJAMIL PADANG HOSPITAL DURING 2016-2018 - Yosep Prabowo; Tutty Ariani (Jurnal Kedokteran Syiah Kuala, 2019)
Abstract. The aging process is unavoidable and sustainable process that concerns the entire organ system. According to the World Health Organization (WHO), geriatrics are individuals over 60 years old. The large number of elderly Indonesian people will have various health problems in the future. Objective: To find out the profile of skin and genital diseases in geriatrics at the dermatology venereology department of Dr. M. Djamil Padang hospital from January 2016 to December 2018. Method: Retrospective study with descriptive design from the patient's medical record data. Results: During the period of January 2016 to December 2018, there were 210 (14,1%) new geriatric patients from total visits of geriatric patients. Those new patients consist of 109 male (51,9%) and 101 women (48,1%) patients. Top five of skin diseases having great number in occurrences were erythropapuloskuamosa (23,3%), tumors (20%), dermatitis (12,9%), fungal infections (11,9%) and viral infections (10,5%). The most common types of erythropapuloskuamosa are seborrheic dermatitis (44,9%), erythroderma (28,6%), and psoriasis (26,5%). Conclusion: New geriatric patients who visited the dermatology and venerology polyclinic in this study were 210 people, there are more male than female and the most types of skin diseases were seborrheic dermatitis.Keyword: geriatric, skin disease, retrospective study